PENGARUH BEBAN KERJA, MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWANPADA PDAM TIRTA SANJUNG BUANA SIJUNJUNG - Seprizal Wira Saputra; Doni Marlius (Jurnal Bina Bangsa Ekonomika, 2024)
The purpose of this research is to examine the influence of workload variables, work motivation and job satisfaction on employee performance at PDAM Tirta Sanjung Buana Sijunjung. This type of research uses quantitative methods. Data collection is done by distributing questionnaires to 79 respondents. The sampling technique used is the Saturated Sampling Technique, namely the sample determination technique when all members of the population are used as samples, using instrument testing (validity test and reliability test). ), classical assumption tests (normality test, multicollinearity test and heteroscedasticity test) then multiple linear regression and hypothesis testing with the help of the SPSS application. The results of the research show that workload has no significant effect on employee performance, work motivation has a positive and significant effect on employee performance, and job satisfaction has a positive and significant effect on employee performance